Penerimaan Ibu dengan Anak Berkebutuhan Khusus ditinjau dari Dukungan Sosial - Damayanti, Esti; Wulandari, Intantri; Safitri , Rizky (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
The purpose of this study was to determine the relationship between social support and acceptance of mothers who have children with special needs. The hypothesis of this study is that there is a positive relationship between social support and the acceptance of mothers who have children with special needs. The subjects in this study were housewives who have children with special needs with a total of 30. The measurement tools used were the scale of social support and the scale of parental acceptance. The data analysis technique uses product moment correlation from Karl Pearson. The results of the study show that there is a very significant positive relationship between social support and acceptance by mothers of children with special needs with r = 0,770 and p = 0,00 (p<0,05) so that it can be said that the hypothesis is accepted.